The Applications of Nano‐Hetero‐Junction in Optical and Thermal Catalysis. Issue 13 (9th March 2016) - Liao, Fenglin; Lo, Benedict T. W.; Tsang, Edman
Abstract: Semiconductors, metal oxides in particular, are usually regarded as key components in most industrial catalysts. It has been reported that the band structures of semiconductors can significantly influence their catalytic properties. As one of the most effective methods for tuning the band structure of semiconductors, the establishment of nano‐hetero‐junctions in catalysts is attracting increasing attention due to the use of rational design and the facile synthesis procedure. This Microreview covers the applications of nano‐hetero‐junctions in both photocatalytic and traditional thermal catalytic reactions. The applications of these reactions range from removal of pollutants to renewable energy production to new chemical synthesis routes, all of which are closely knitted into our daily lives. In photocatalysis, improvement is mainly attributed to the separation of photogenerated electrons and holes, which prolongs their lifetimes and eventually allows the occurrence of chemical reactions with adsorbed substrate molecules. Our research group were amongst the first to apply this concept in the design of metal/metal oxide catalysts in traditional thermal catalysis. It has been found that the establishment of electronic nano‐hetero‐junctions in support materials with use of two semiconducting metal oxides of different energy levels influences the catalytic properties of the dispersed metal particles from two perspectives: (i) the potential energy upon excitation, created by the charge separation on semiconducting oxide support in proximity to the overlying metal particles, and (ii) under H2, the accumulated electrons on one semiconducting oxide support can facilitate direct reduction of metal cations in this support to metal atoms, while the accumulated holes (activated oxygen) on the other semiconducting oxide are relaxed by water formation through hydrogen oxidation. The metallic atoms from the support surface thus act as modifiers to the primary metal particles through the formation of a bimetallic phase. As a result, the electronic configuration of the supported metal particles can be modified in a subtle manner that consequently influences the catalytic performance. It is believed that this concept of designing nano‐hetero‐junctions should empower scientists to approach new catalytic reactions in a systematic manner, allowing fine‐tuning of catalysts with superior performance. Abstract : Heterojunction of two semiconductor phases to prolong lifetimes for spatial charge separation is a well‐established concept in photophysics and is widely explored in solar cell and photocatalytic devices. However, its applications in thermal catalysis are currently rather limited. This Microreview covers the applications of nano‐hetero‐junctions in thermal catalysis and photocatalysis.